Perpaduan Metode Certainty Factor dan Forward Chaining untuk Menentukan Tingkat Stres Mahasiswa Tingkat Akhir Berbasis Android - Nurholis Nurholis; Fauziah Fauziah; Novi Dian Natashia (KITA Institute, 2021)
Students who are taking the final semester are students who are completing all their subjects, can take the final project provided they have met the number of credits set to obtain a bachelor's degree. In the process of making a final project, students are required to complete it within a predetermined time, this demand causes students to be depressed, causing stress that affects them in completing their final project and study period. Based on this problem, an Expert System Application was made to Diagnose Stress Levels in Final Year Students by Combining Certainty Factor Methods and Android-Based Forward Chaining Techniques to find out more clearly the level of stress experienced by final year students. The results of the diagnosis on the expert system application and the results of manual calculations on one of the data which is representative of the 200 student data, which produce the same level of confidence, each of which produces a confidence level of 97.97% and was diagnosed with mild stress.